ANALISIS TERHADAP PELANGGARAN KODE ETIK NOTARIS SEBAGAI PEJABAT UMUM DI KOTA MEDAN - TASYA ANINDITA (PREMISE LAW JURNAL, 2018)
DOSEN PEMBIMBING:1. Budiman Ginting2. Saidin3. Syafnil Gani Every professional organization has its own code of ethics as the guideline for its members’ behavior. Ethics is a critical, methodical, and systematic reflection of human behavior concerning human good and bad norms and behavior. Article 1, figure 2 of Notarial Code of Ethics of the INI (Indonesian Notarial Association) deals with the moral principle determined by and based on the Decision of the Congress of the INI. As a public official who serves people, he can have personal and occupational errors. The imposition of sanction on the violation against the code of ethics is adjusted to the quantity and quality of the violation. By viewing the Notarial Act and the Notarial Code of Ethics, we can see how fat the upholding of law in violation of the code of ethics done by a Notary as the public official in Medan.Keywords: Notary, Code of Ethics, Notarial Honorary Council